BIBLIOMETRIC ANALYSIS OF PHYSICS LEARNING RESEARCH TRENDS USING SOCIO-SCIENTIFIC ISSUES IN THE LAST 10 YEARS - Wulandari, Novita; Jumadi, Jumadi; Laeli, Silvia; Kuswanto, Heru (JURNAL EDUSCIENCE, 2025)
Purpose-Contextual learning approaches play an important role in supporting the needs of 21st-century Education. Socioscientific issues (SSI) orientation is one form of contextual approach that is relevant to physics learning. This study aims to see research trends on socioscientific issues in the period 2014 to 2023. The main focus of this study is to understand the role of SSI in supporting the development of 21st-century skills.Methodology-This type of research includes literature using bibliometric analysis methods. The data analysis process used VOSviewer software to obtain a network visualization that states the relationship between keywords.Findings-The synthesis results refer to the distribution of articles per year, research themes, countries of affiliation, and authors. One hundred articles were successfully identified through the Scopus database, showing that research on socioscientific issues fluctuates yearly. Based on bibliometric analysis, the keyword "socioscientific issues" is closely related to students' scientific literacy attitudes and abilities. This relationship highlights the importance of socioscientific issues in learning, especially in helping students understand scientific issues relevant to everyday life.Significance-Research also shows that integrating sociocultural issues in learning plays an important role in supporting the development of 21st-century skills. Therefore, the relevance of Socioscientific Issues can be applied by teachers in physics learning.Keywords: Bibliometric; physics; science; socio-scientific issues